Policy Communities and Natural Disasters: Cyclone Eline and Idai in Zimbabwe - Mutizwa, Bismark (International Journal of Law and Public Policy (IJLAPP), 2023)
Zimbabwe is vulnerable to natural disaster of various kinds including earthquakes but the most common and destructive have been cyclones which appear to be more frequent and aggressive in recent years. This paper seeks to explore the heuristic value of the concept of policy community in understanding how cyclones are dealt with throughout the natural disaster cyclone. As such, the paper`s ambition is not so much to understand cyclones as natural disasters - admittedly an important subject on its own - but to dissect how policy stakeholders i.e those who are affected and want to affect the policy problem respond to cyclones that ravage Zimbabwe, especially the eastern part of the country.